2014
DOI: 10.1007/s40519-014-0131-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of orthorexia nervosa among ashtanga yoga practitioners: a pilot study

Abstract: The results of this pilot study should suggest ashtanga yoga teachers to avoid excessive reference to a healthy diet, which is natural component of yoga practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
56
5
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(77 citation statements)
references
References 13 publications
11
56
5
5
Order By: Relevance
“…Our results indicated that vegetarian diet was directly associated with higher levels of all aspects of orthorexia nervosa (knowledge of healthy eating, problems associated with healthy eating and feelings positively about healthy eating) (H1 was confirmed). These findings are in line with prior studies in the literature that also find that higher rate of orthorexic behaviors was linked to a vegetarian diet [12,17,[40][41][42]. It can be supposed that a vegetarian diet might increase the risk of developing orthorexia nervosa [11].…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicated that vegetarian diet was directly associated with higher levels of all aspects of orthorexia nervosa (knowledge of healthy eating, problems associated with healthy eating and feelings positively about healthy eating) (H1 was confirmed). These findings are in line with prior studies in the literature that also find that higher rate of orthorexic behaviors was linked to a vegetarian diet [12,17,[40][41][42]. It can be supposed that a vegetarian diet might increase the risk of developing orthorexia nervosa [11].…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of ON in the current study population is reflected in previous studies, where higher prevalence was found in yoga instructors (86%) [30], dieticians (41.9%) [31], nutrition students (35.9%) [32], exercise science students (84.5%) [33], and patients recovering from AN or bulimia nervosa (58%) [40] compared to the general population (<1%) [29, 34]. These are all populations who take an active interest in their health and body, in the same way that the healthy eating community on Instagram might be.…”
Section: Discussionmentioning
confidence: 53%
“…Currently the ORTO-15 questionnaire [29] is used to determine the presence of ON. Higher prevalence has been found in yoga instructors [30], dieticians, [31], nutrition students [32], and exercise science students [33] compared to the general population. The prevalence of ON in the general population was recently estimated to be less than 1% [34].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first studies, a growing body of evidence has developed showing that ON is frequently observed in bothgender athletes [21], ballet dancers [27], yoga practitioners [28], and healthcare professionals [29] among others. Most of them are groups of population concerned or interested in their own body to achieve a good physical performance.…”
Section: Discussionmentioning
confidence: 99%